The Influence Of Digital Marketing, Product Quality, And Online Customer Reviews On The Purchase Decisions Of Maybelline Cosmetic Products Among Students In Surabaya - Susanti, Dewi; Soebiantoro, Ugy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Digitalization has changed the way cosmetic companies operate, market their products, and interact with consumers. One company that has excellent cosmetic product quality and continues to innovate as time goes on is Maybelline. Maybelline leverages the power of social media to introduce new products, share makeup tutorials, and interact directly with consumers. The objective is to determine the influence of digital marketing, product quality, and online customer reviews on purchasing decisions. This study employs a non-probability sampling method using purposive sampling. The sample size consists of 152 respondents. Based on the results of the SEM Partial Least Squares (PLS) version 4.0 data analysis, it is evident that digital marketing, product quality, and online customer reviews have a positive and significant influence on the decision to purchase Maybelline cosmetic products. The findings of this study indicate that intensive digital marketing, high-quality products, and numerous positive reviews will drive purchase decisions for Maybelline cosmetic products and maintain their position in the competitive beauty market.